1997
DOI: 10.1002/(sici)1096-8628(19970414)69:4<380::aid-ajmg8>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 16 cystic fibrosis mutations in Mexican patients

Abstract: We carried out molecular analysis of 80 chromosomes from 40 unrelated Mexican patients with a diagnosis of cystic fibrosis. The study was performed in two PCR steps: a preliminary one to identify mutation delta F508, the most frequent cause of cystic fibrosis worldwide, and the second a reverse dot-blot with allele-specific oligonucleotide probes to detect 15 additional common mutations in the Caucasian population. A frequency of 45% for delta F508 was found, making it the most common in our sample of Mexican … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These results are similar to those of another study performed in northeastern Mexico (Villalobos et al 1997), where 16 different CF mutations were screened in a sample of 40 patients and 56.3% CF chromosomes were characterized. We found that the ∆F508 mutation frequency in our study population was very low (40.7%) and similar to the 45% (Villalobos et al 1997) and 34.4% (Flores et al 1997) found in other regions of Mexico. The G542X mutation has a frequency higher (6.1%) than that reported to the CFGAC, but similar to Spanish patients (Casals et al 1997).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those of another study performed in northeastern Mexico (Villalobos et al 1997), where 16 different CF mutations were screened in a sample of 40 patients and 56.3% CF chromosomes were characterized. We found that the ∆F508 mutation frequency in our study population was very low (40.7%) and similar to the 45% (Villalobos et al 1997) and 34.4% (Flores et al 1997) found in other regions of Mexico. The G542X mutation has a frequency higher (6.1%) than that reported to the CFGAC, but similar to Spanish patients (Casals et al 1997).…”
Section: Discussionmentioning
confidence: 90%
“…This first part of the study enabled us to characterize only 56.66% of the CF chromosomes in the Mexican population. These results are similar to those of another study performed in northeastern Mexico (Villalobos et al 1997), where 16 different CF mutations were screened in a sample of 40 patients and 56.3% CF chromosomes were characterized. We found that the ∆F508 mutation frequency in our study population was very low (40.7%) and similar to the 45% (Villalobos et al 1997) and 34.4% (Flores et al 1997) found in other regions of Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, this work may be comparable with modifier genes studies performed in those countries. Two previous CFTR mutation reports in the Mexican population showed ΔF508 frequencies of 40.72% [25], 45% [26] and 44.6% [27]. Differences could be explained by the clinical criteria, geographic origin and the analytical methods available at that time.…”
Section: Discussionmentioning
confidence: 91%